Ca2+ permeation in cyclic nucleotide‐gated channels - Dzeja, Claudia; Frings, Stephan (The EMBO journal, 1999)
Cyclic nucleotide‐gated (CNG) channels conduct Na+, K+ and Ca2+ currents under the control of cGMP and cAMP. Activation of CNG channels leads to depolarization of the membrane voltage and to a concomitant increase of the cytosolic Ca2+ concentration. Several polypeptides were identified that constitute principal and modulatory subunits of CNG channels in both neurons and non‐excitable cells, co‐assembling to form a variety of heteromeric proteins with distinct biophysical properties. Since the contribution of each channel type to Ca2+ signaling depends on its specific Ca2+ conductance, it is necessary to analyze Ca2+ permeation for each individual channel type. We have analyzed Ca2+ permeation in all principal subunits of vertebrates and for a principal subunit from Drosophila melanogaster . We measured the fractional Ca2+ current over the physiological range of Ca2+ concentrations and found that Ca2+ permeation is determined by subunit composition and modulated by membrane voltage and extracellular pH. Ca2+ permeation is controlled by the Ca2+‐binding affinity of the intrapore cation‐binding site, which varies profoundly between members of the CNG channel family, and gives rise to a surprising diversity in the ability to generate Ca2+ signals.